BASED ON THE COGNITIVE AND BEHAVIORAL APPROACH, CAN KNOWING ABOUT SEXUALITY IN THE 21st CENTURY PROMOTE HEALTH? - Priscila de Souza Fernandes, Thaynara (Revista Gênero e Interdisciplinaridade, 2023)
This article unites sexuality and the cognitive and behavioral approach to present some of the main beliefs surrounding the theme, which, at the present time, is slowly breaking away from taboos and enigmas within the constant scientific revolutions of the 21st century. By analyzing some discourses of the cognitive and behavioral model, health and sexuality, we can identify the dynamic constructs that involve them and establish a healthier vision for men and women in general, since the importance of disseminating the subject with quality is evident, as surveyed by the World Health Organization (WHO). Thus, giving theoretical support to professionals to work on the theme, which is on a growing trend, has great social importance, since, as the belief and interpretation of events are motivating factors based on the therapeutic approach of cognition and behavior, when contributing to areas of interest such as medicine, psychology and sexology, through the archeology of knowledge about sexuality and the implication of beliefs, one definitely gains more health, because what perpetuates its dysfunctionalities and its prejudices is the lack of knowledge or the inaccessibility of works already produced on the subject.